Corporate Sustainability, Social Responsibility and Environmental Management : an Introduction to Theory and Practice with Case Studies - Camilleri, Mark Anthony, 1976- (Springer, 2017)
This book provides a concise and authoritative guide to corporate social responsibility (CSR) and related paradigms, including environmental responsibility, corporate sustainability and responsibility, creating shared value, strategic CSR, stakeholder engagement, corporate citizenship, business ethics and corporate governance, among others. It is primarily intended for advanced undergraduate and / or graduate students. Moreover, it is highly relevant for future entrepreneurs, small business owners, non-profit organisations and charitable foundations, as it addresses the core aspects of contemporary strategies, public policies and practices. It also features case studies on international policies and principles, exploring corporate businesses' environmental, social and governance reporting. "Mark Camilleri's new book provides an excellent overview of the eclectic academic literature in this area, and presents a lucid description of how savvy companies can embed themselves in circular systems that reduce system-wide externalities, increase economic value, and build reputation. A valuable contribution. "Charles J. Fombrun, Founder of Reputation Institute and a former Professor of Management at New York University and The Wharton School, University of Pennsylvania, USA. "The book is a rich source of thought for everyone who wants to get deeper insights into this important topic. This book is a critical companion for academics, students, and practitioners." Adam Lindgreen, Professor and Head of Department of Marketing, Copenhagen Business School, Denmark. "Mark's latest book is lucid, insightful, and highly useful in the classroom. I strongly recommend it." Donald Siegel, Dean of the School of Business and Professor of Management at the University at Albany, State University of New York, NY, USA